Muscle activity in the parallel christie during alpine skiing and while using glestain grandeur as an off-season training device - Katoh, M.; Taniguchi, K.; Inada, N.; Yamada, T. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The efficacy of muscle activity during in-line skating and while alpine slalom skiing has yet to be determined quantitatively (Zeglinksi et al., 1998). Therefore, the purpose of this study was to compare muscle activity during parallel christie on both alpine skis and with the glestain grandeurs, because we feel the glestain grandeur more approximates the side to side movements of alpine skiing than do other dry-land training devices.